2005
DOI: 10.1126/science.1120014
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Property Landscape of the Human Genome

Abstract: The impact of gene patents on downstream research and innovation are unknown, in part because of a lack of empirical data on the extent and nature of gene patenting. In this Policy Forum, the authors show that 20% of human gene DNA sequences are patented and that some genes are patented as many as 20 times. Unsurprisingly, genes associated with health and disease are more patented than the genome at large. The intellectual property rights for some genes can become highly fragmented between many owners, which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(110 citation statements)
references
References 23 publications
0
108
0
Order By: Relevance
“…While making the research results publicly available allows others to build on the invention, as such it also compels others to recognize and respect to the scientific results shown in the invention. Although there have been concerns that increase in university patenting has challenged the open nature of university research and shifted academic research towards more commercialization, a number of scholars have investigated the relationship between patenting and open dissemination of research results by scientists in the forms of publications (Agrawal and Henderson 2002;Jensen and Murray 2005;Van Looy et al 2006). These studies have also found that publication and patenting are complementary and not competing activities of university researchers.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…While making the research results publicly available allows others to build on the invention, as such it also compels others to recognize and respect to the scientific results shown in the invention. Although there have been concerns that increase in university patenting has challenged the open nature of university research and shifted academic research towards more commercialization, a number of scholars have investigated the relationship between patenting and open dissemination of research results by scientists in the forms of publications (Agrawal and Henderson 2002;Jensen and Murray 2005;Van Looy et al 2006). These studies have also found that publication and patenting are complementary and not competing activities of university researchers.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Most of these studies have found a positive relationship between scientific publication and patenting activities. Jensen and Murray (2005) stated that most university research generates dual outcomes which can be utilized as paper-patent pairs. Scientific publications will follow as in most cases a research project can generate outputs that simultaneously contribute to public knowledge and to commercialization.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The data do show a large number of patents associated with genes. A recent study found that nearly 20% of human genes were associated with at least one U.S. patent, and many had multiple patents [20]. Another study estimated that in the U.S. over 3000 new DNA-related patents have issued every year since 1998, and more than 40,000 such patents have been granted [7].…”
Section: Reflecting On the Evidencementioning
confidence: 99%
“…In 2005, researchers reported that 20% of human genes had been patented 1 . Two weeks ago, another team raised that estimate to at least 41% (ref.…”
Section: W Hen Daniel Weaver Pitchesmentioning
confidence: 99%